Automated pupillometer for monitoring the critically ill patient: A critical appraisal - Zafar, Sahar F.; Suarez, Jose I. (Journal of critical care, 2014)
Abnormalities in the pupillary light reflex are an important prognostic indicator for patients in the intensive care unit (ICU). Manual pupillary examination is confounded by interobserver discrepancies and errors in detecting a reflex under certain conditions. The automated pupillometer is a computer-based infrared digital video device that can obtain objective measurements of pupillary size and reactivity. We performed an electronic literature search to identify original studies on the use of the automated pupillometer in the ICU. We identified 7 articles that met the inclusion criteria and reviewed them critically and assessed the quality of evidence by using the Grading of Recommendations Assessment, Development, and Evaluation approach. We found that the study grade was low, and study quality was low to moderate for all the reviewed manuscripts. Pupillometric measurements had better precision and reproducibility compared with the manual pupillary examination. Based on these data, we conclude that pupillometry monitoring can serve as an important tool in the ICU. Further large scale studies on patients in the neurocritical care unit and medical ICU are needed to support the routine use of automated pupillometry.